Resiliencia, disposición al cambio, balance trabajo familia en trabajadores (España y Colombia) - García Rubiano, Mónica (2024)
This research aimed to analyze the positive effect of willingness to change in its three dimensions (individual, group and organizational), on the generation of personal resources in employees and their perceived balance between work and life. The participants were 320 employees from different companies in Colombia and Spain. Sampling was for convenience. The results show the positive effect of the three levels of acceptance of change, both with the generation of new personal resources and with resilience; as well as with the perception of work-family balance. From this can be inferred the importance for organizations of generating policies aimed at promoting the acceptance of change in work teams and at a global level.